Extensiveness and homogeneity of diabetic/non-diabetic patients and their co-relation with CBNAAT confirmed tuberculosis patients in a tertiary care hospital of India - Bisht, Himanshu Singh; Rajput, Madhurendra Singh; Tiwari, Sanchit; Kaur, Sunpreet; Gaur, Vivek (International Journal of Research in Medical Sciences, 2022)
Background: Many studies reported association between TB susceptibility and diabetes mellitus (DM). Some studies were retrospective, did not assess other co morbidities related with tuberculosis. The effects of diabetes on tuberculosis severity (EDOTS) can be hypothesizing that burden of cases India is leading in TB and runner-up in diabetic. We report interim findings after enrolling 732 of a planned 212 subjects. Methods: This study conducted on patients with TB in west India with DM and normoglycemia defined by glucose tolerance test (GTT) and glucose fasting. Glycocylated hemoglobin (HbA1c), lipids profile and 25-hydroxyvitamin D were measured at the time of enrollment of patients. All patients were monitored monthly while they visited in TB and chest clinic for TB treatment. Results: Of 212 eligible patients, 117 (55.18%) were classified as diabetic, 49 (23.11%) with pre diabetic history (PDM), and 46 (21.70%) as normoglycemic (NG). DM patients were more likely to have a family history of diabetes in comparison to NG patients. Low density lipoprotein (LDH)) was higher in KDM as compared with NDM and NG patients. More patients (32) found diabetic through OGTT as compared with HbA1c (29). Conclusions: Early EDOTS, glycemic control and improve lifestyle can reduce the heterogeneity and implications for the TB-DM. Early diagnosis of TB and DM plays an important role in the management and treatment of TBDM.